Invasive infection caused by Klebsiella pneumoniae is a disease affecting patients with high comorbidity and associated with high long-term mortality - Vading, M.; Nauclér, P.; Kalin, M.; Giske, C. G. (PLOS ONE, 2018)
Klebsiella pneumoniae (KP) is after Escherichia coli (EC) the most common gram-negative species causing invasive infections. Herein, we analyzed risk factors and prognosis in invasive infections caused by KP versus EC, in an area with low antimicrobial resistance. Moreover, we compared antimicrobial resistance and relative prevalence of KP and EC (KP/EC-ratio) in different European countries, using EARS-Net data. Adult patients admitted to Karolinska University Hospital 2006–2012 with invasive infection caused by KP (n = 599) were matched regarding sex and age with patients infected by EC. The medical records were retrospectively reviewed. Comorbidity was adjusted for with multivariable analysis. European data were retrieved from the EARS-Net database. No differences were observed in 7- and 30-day mortality between the groups. The 90-day mortality was significantly higher in the KP cohort (26% versus 17%, p<0.001), but not after adjusting for comorbidity. Malignancy was seen in 53% of the patients with KP versus 38% with EC, OR 1.86 (1.34–2.58). A significant increase in the rate of ESBL-production was observed in EC, but not in KP. The KP/EC-ratio remained stable. In contrast, European data showed increasing percentages of isolates non-susceptible to third-generation cephalosporins in EC and KP, and increasing KP/EC-ratio. Invasive infection caused by KP is a disease affecting patients with high comorbidity and associated with high 90-d mortality. The stable KP/EC-ratio and low occurrence of antimicrobial resistance in data from Karolinska University Hospital compared to aggregate data from 20 EARS-Net countries could be related to absence of clonal spread of multidrug-resistant KP.